English L1 Interference on Spanish as a Foreign Language Written Production: Study Based on a Computerized Corpus of Learners - Núñez Nogueroles, Eugenia Esperanza; Ruiz-Cecilia, Raúl (Didáctica. Lengua y Literatura, 2022)
This paper explores the interference that the learner’s mother tongue (L1) exerts on the written production in the foreign language. In this study, 50 texts produced by Spanish as a Foreign Language beginner (A1 and A2) pupils ‒whose native tongue is English‒ were examined. The sample was extracted from a freely available corpus. Results showed that students belonging to A2 level made twice as many errors as the learners placed in A1. This outcome leads us to reflect upon the necessity of dealing with linguistic interference in order to avoid future fossilisations. According to this piece of research, the following error types should be prioritised: morphological and lexical-semantic (grammatical criterion), and wrong selection and reverse order (linguistic criterion).
Keywords: error analysis; computerised learner corpora; Spanish as a foreign language; L1 interference; written production